1985
DOI: 10.1172/jci111805
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the difference in urine and blood carbon dioxide tension during bicarbonate loading as an index of distal nephron acidification in experimental models of distal renal tubular acidosis.

Abstract: Recent classifications of the several pathophysiologic types of distal renal tubular acidosis (secretory, voltage dependent, and gradient) have been based on the response of acidification parameters to a series of provocative maneuvers in vivo and in vitro. A reduction in the difference in urine and blood CO2 tension during bicarbonate loading (U-B pCO2 gradient), a widely applied parameter, has been employed as an index of reduced distal nephron proton secretion. This study was designed to test the validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 30 publications
(32 reference statements)
5
40
0
Order By: Relevance
“…Second, in the latter study (36) systemic respiratory alkalosis (Paco2 = 27 mmHg) was present. Third, urinary Pco2, even in sham controls receiving bicarbonate, was much lower in the previous study (53 mmHg) than that routinely observed in bicarbonate loaded control rats in our laboratory (100-120 mmHg) (14) (27). Compatible with our data, however, Robson et al (37) have reported that mineralocorticoid (9-afluorohydrocortisone) administration to adrenal intact rabbits increased the U-B Pco2 relative to controls undergoing a similar bicarbonate diuresis.…”
Section: Effects Ofcmasupporting
confidence: 64%
See 3 more Smart Citations
“…Second, in the latter study (36) systemic respiratory alkalosis (Paco2 = 27 mmHg) was present. Third, urinary Pco2, even in sham controls receiving bicarbonate, was much lower in the previous study (53 mmHg) than that routinely observed in bicarbonate loaded control rats in our laboratory (100-120 mmHg) (14) (27). Compatible with our data, however, Robson et al (37) have reported that mineralocorticoid (9-afluorohydrocortisone) administration to adrenal intact rabbits increased the U-B Pco2 relative to controls undergoing a similar bicarbonate diuresis.…”
Section: Effects Ofcmasupporting
confidence: 64%
“…Based on these previous findings we would predict that disequilibrium pH would also be reduced or obliterated in rats with aldosterone deficiency, although, such data are not available at present. In the defects associated with the postobstructed kidney and amiloride, a minimal urine pH cannot be achieved either with an acute acid load alone, or after superimposed sodium sulfate infusion (27). Since a normal minimal urine pH can be achieved in SAD in association with low buffer excretion, this finding in conjunction with the findings in the present study implies that a direct effect of aldosterone on H+ secretion may be quantitatively more important than indirect effects mediated through voltage changes.…”
Section: Effects Ofcmasupporting
confidence: 46%
See 2 more Smart Citations
“…Urine pCO 2 may have a number of origins, including delayed dehydration of carbonic acid, trapping of CO 2 in the countercurrent system, mixture of urines at different pH values from different nephrons, and ampholyte properties of bicarbonate buffer, among others (16). However, U-B pCO 2 has also been considered to represent the magnitude of distal nephron (mostly collecting duct) H + -ion secretion at high urinary bicarbonate concentrations (17,18). In these experiments, corticosterone (B), aldosterone (A) or 18-OH corticosterone (18-OH-B) was given to ADX rats in order to investigate the role of each of them in supporting the normal rate of renal tubule H + secretion.…”
Section: Introductionmentioning
confidence: 99%